Understanding the treatment response and resistance to targeted therapies in non-small cell lung cancer: clinical insights and perspectives - Zhang, Hang; Zhang, Yingying; Zhu, Yingying; Dong, Tian; Liu, Zheng (Frontiers in Oncology, 2024)
Lung cancer remains the leading cause of mortality worldwide. Non-small cell lung cancer (NSCLC) is the most common subtype of lung cancer with a generally poor prognosis. In recent years, advances in targeted therapy and sequencing technology have brought significant improvement in the therapeutic outcomes of patients with advanced NSCLC. Targeted inhibitors directed against specific mutated or rearranged oncogenes, such as epidermal growth factor receptor (EGFR), anaplastic lymphoma kinase (ALK), and receptor tyrosine kinase ROS proto-oncogene 1(ROS1) among others, exhibit promising anti-tumor activity. Unfortunately, some patients develop acquired resistance and disease progression soon after initial remission. Despite the continuous development of new drugs and strategies to overcome drug resistance, it is still a major challenge in the treatment of NSCLC. The landscape of targeted therapy for NSCLC is evolving rapidly in response to the pace of scientific research. Accordingly, this updated study aimed to comprehensively discuss the tumor target antigens and targeted therapy-related agents in NSCLC.